The The effect of sterilization time on oil loss into the condensate water of sterilizer in the crude palm oil industry - Sri Rizki Putri Sri Primandari; Mulianti Mulianti; Harumi Veny (Jurnal Teknik Kimia, 2023)
Sterilization in the sterilizer unit is one of the important processes in the Crude Palm Oil (CPO) industry but it can cause oil loss in the palm fruit which reduces the oil yield if the sterilization process is carried out over time. Therefore, the sterilization time needs to be considered so that this study aims to analyze the effect of the length of Fresh Fruit Bunches (FFB) sterilization time on oil loss in condensate water sterilizer on the industry of CPO and determine the maximum time in the Sterilizer. This study was conducted at a CPO plant in West Sumatra with a maximum standard of 1.2 % oil loss, the optimum sterilization time can be determined. This study uses a horizontal-type sterilizer through a triple-peak sterilization system. Peak pressure 1 is 1.2 bar; peak pressure 2 is 2.0 bar; and the triple peak pressure is 3.0 bar with a temperature of 130-140 °C. The time varies from 83 – 90 minutes. The results showed that the longer the sterilization time, the greater the percentage of oil loss. In conclusion, the maximum time in sterilizer is achieved under 87.4 minutes with an maximum oil loss standard of 1.2 %.